UPAYA KEPALA MADRASAH DALAM MENINGKATKAN KUALITAS SISWA DI MA TAHFIDZ AL-QUR’AN PESANGGARAN BANYUWANGI - Nur Hidayati; Khabib Sharifudin (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
This research was motivated by an increase in the quality of students at MA Tahfidz Al-Qur'an in Sumbermulyo village, Pesanggaran Banyuwangi, since the leadership of the madrasah head Ahmad Jafarudin SE, previously the number of students was small, the quality of learning was still low and the image of MA Tahfidz Al-Qur'an in Sumbermulyo village Banyuwangi Pesanggaran which is now an escape school or exile school. The purpose of this study is to examine the efforts of the head of the madrasa in improving the quality of students as well as the obstacles and solutions at MA Tahfidz Al-Qur'an in the village of Sumbermulyo Pesanggaran Banyuwangi. This study used qualitative research methods. While collecting data by observation, interviews, and documentation. The data analysis uses data reduction techniques, data presentation, and draw conclusions. The sources of information in this review consist of important sources of information obtained from madrasa heads, homeroom teachers, and teachers and additional sources of information obtained from reports and photos about MA Tahfidz Al-Qur'an Sumbermulyo Pesanggaran Banyuwangi. The results of this study are that the head of the madrasa maximizes his duties in leading his institution, and the efforts of the head of the madrasa to improve the quality of students at MA Tahfidz Al-Qur'an include providing opportunities for teachers to improve their skills well and skilled, providing facilities and infrastructure so that the learning process runs more smoothly and generates student motivation, while a few obstacles such as discipline and student behavior can be overcome by providing understanding and the passage of time.